Preparation of tender document / Muhammad Fauzi M Haron - M Haron, Muhammad Fauzi (2010)
The report, in brief, is about the procedure and process to the preparation of tender documents, the basic compulsory content and common aspect in tender documents based on the six months' internship experiences. The report is partial into several chapter begins with the background of the company profile, theoretical review on the topic, case study and problems with solutions. Background of company profile named ARH Juruukur Bahan Sdn. Bhd. includes the staff list, company's history and their list of completed projects. Most of the aspect in theoretical review is ranging only in pre-contract stages start from estimation process until invitational to tender. However, the compulsory or general contents of tender documents are best described. The compulsory contents described are based on format used by ARH Juruukur Bahan Sdn. Bhd., please note that contents of tender documents may vary according to types of project. The case study review is adapted from the interview with the experienced Quantity Surveyors. Through the interview, the writer has been able to understand the nature situation about his review topic. Problems and solutions section made, also adapted from the interview, are the best common scenario happened during the preparation of tender documents. The effective solutions are issued as a closing section of the report to solve all general problems occurred. After gone through all the pages of the report, the readers may found certain terms and words used as an introduction to tender documents. In conclusion, the report is hopefully to be a quick guide handbook to all readers about the content of tender documents.